ALKBH5-mediated m6A mRNA methylation governs human embryonic stem cell cardiac commitment - Zhenbo Han; Zihang Xu; Ying Yu; Yang Cao; Zhengyi Bao; Xinlu Gao; Danyu Ye; Gege Yan; Rui Gong; Juan Xu; Lai Zhang; Wenya Ma; et al. (Elsevier, 2021)
N6-methyladenosine (m6A), as the most abundant modification of mammalian messenger RNAs, is essential for tissue development and pathogenesis. However, the biological significance of m6A methylation in cardiac differentiation and development remains largely unknown. Here, we identify that the downregulation of m6A demethylase ALKBH5 is responsible for the increase of m6A methylation and cardiomyocyte fate determination of human embryonic stem cells (hESCs) from mesoderm cells (MESs). In contrast, ALKBH5 overexpression remarkably blocks cardiomyocyte differentiation of hESCs. Mechanistically, KDM5B and RBBP5, the components of H3K4 modifying enzyme complexes, are identified as downstream targets for ALKBH5 in cardiac-committed hESCs. Loss of function of ALKBH5 alters the expression of KDM5B and RBBP5 through impairing stability of their mRNAs, which in turn promotes the transcription of GATA4 by enhancing histone H3 Lys4 trimethylation (H3K4me3) at the promoter region of GATA4. Taken together, we reveal a previously unidentified role of m6A demethylase ALKBH5 in determining cardiac lineage commitment of hESCs.